The Influence of Current Ratio, Debt to Equity Ratio and Company Size on Return On Assets - et. al., Dede Hertina, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to determine the effect of Current Ratio, Debt To Equity Ratio and Company Size on Return On Assets. The study population was all food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the period 2014-2018. The research sample that met the criteria using purposive sampling method, there were 9 companies. This research uses descriptive and verification methods and the type of research is quantitative. The data analysis method used is panel data regression analysis (Fixed Effect). The results of the study show that simultaneously Current Ratio, Debt To Equity Ratio and Company Size have an effect on profitability. Partially Current Ratio and Debt To Equity Ratio have no effect on Return on Assets, and Company Size has a significant negative effect on Return on Assets.